Membangun Jiwa Entrepreneurship Dalam Kerjasama Tim - Ferdian Arie Bowo; Asep Saepullah (Manajerial, 2021)
The purpose of this research to analyze the spirit of entrepreneurship in teamwork using descriptive methods. Data collection techniques use literature studies, observations and documents. The results showed that teamwork is an inseparable part of human life as social beings who need each other. Without cooperation, humans will feel difficulties in overcoming various kinds of social problems that occur in society. By building a spirit of entrepreneuship in teamwork, we can foster an attitude of discipline, high commitment, honesty, creative and innovative, independent and realistic